2018
DOI: 10.24912/jk.v10i1.1282
|View full text |Cite
|
Sign up to set email alerts
|

Pembentukan Harga Diri: Analisis Presentasi Diri Pelajar SMA di Media Sosial

Abstract: Self-presentation is a specific action of self-disclosure presenting a positive impression to others. Self-presentation is rapidly growing by the presence of various social media, esppecially Instagram. Instagram as one of social media with a various features and large user, bring major affect to teenager’s presentation of self in the media. This is inseparatable part of teenager process in searching their indentity. This research conducted in SMA Negeri Mojogedang by taking sample of 264 students. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…The majority of these actions were carried out by young people, according to information from RSUD dr. Soetomo stated that on average ten teenage patients come every week with scratches, scratches or bumps against walls (Tarigan & Apsari, 2021). In 2023, a report from SMP Negeri 1 Ngariboyo, Magetan Regency, East Java, revealed that 76 students were identified as committing acts of self-harm, including cutting their wrists with sharp objects such as razors, needles, broken glass and rulers (Adhitama, 2023).…”
Section: Self-defeating Behaviormentioning
confidence: 99%
“…The majority of these actions were carried out by young people, according to information from RSUD dr. Soetomo stated that on average ten teenage patients come every week with scratches, scratches or bumps against walls (Tarigan & Apsari, 2021). In 2023, a report from SMP Negeri 1 Ngariboyo, Magetan Regency, East Java, revealed that 76 students were identified as committing acts of self-harm, including cutting their wrists with sharp objects such as razors, needles, broken glass and rulers (Adhitama, 2023).…”
Section: Self-defeating Behaviormentioning
confidence: 99%
“…Presentasi dibawakan oleh pemateri secara menyenangkan dan menarik dengan berbagai kisah atau pengalaman bisnis langsung dari pemateri. Tujuan akhir dari metode ini adalah agar siswa/i mengerti apa materi yang disampaikan sehingga dapat diterapkan di kehidupan sehari-hari (Purworini, 2018: (Setiawati et al, 2018. Metode tanya jawab dilakukan pada kegiatan IBM Goes to School.…”
Section: Metode Pelaksanaanunclassified